A pan-cancer landscape of IGF2BPs and their association with prognosis, stemness and tumor immune microenvironment - Wei Shao; Hui Zhao; Shoudu Zhang; Qian Ding; Yugang Guo; Kaiqi Hou; Yunchao Kan; Fan Deng; Qian Xu (Frontiers in Oncology, 2023)
BackgroundThe human insulin-like growth factor 2 mRNA binding proteins 1–3 (IGF2BP1–3, also called IMP1–3) play essential roles in mRNA regulation, including its splicing, translocation, stability, and translation. However, knowledge regarding the involvement of IGF2BPs in tumor immunity and stemness across cancer types is still lacking.MethodsIn this study, we comprehensively analyzed pan-cancer multi-omic data to determine the correlation of IGF2BPs mRNA and protein expression with various cancer parameters such as mutation frequency, prognostic value, the tumor microenvironment (TME), checkpoint blockade, tumor immune infiltration, stemness and drug sensitivity. Validation of the expression of IGF2BPs in cancer samples and glioma cells were performed by quantitative real-time (qRT)-PCR, and immunofluorescence staining. Investigation of the functional role of IGF2BP3 in glioma stem cells(GSCs) were performed by sphere formation, cytotoxicity, transwell, and wound healing assays.ResultsWe found that IGF2BP1 and 3 are either absent or expressed at very low levels in most normal tissues. However, IGF2BP1-3 can be re-expressed in a broad range of cancer types and diverse cancer cell lines, where their expression often correlates with poor prognosis. Immunofluorescence staining and qRT-PCR analyses also showed that the expression of IGF2BP2 and IGF2BP3 were higher in cancer tissues than that in adjacent normal tissues. Moreover, IGF2BPs are associated with TME and stemness in human pan-cancer. Remarkably, IGF2BP3 participated in the maintenance and self-renewal of glioma stem cell (GSCs). Knockdown of IGF2BP3 attenuated GSC and glioma cell proliferation, invasion, and migration.ConclusionsOur systematic pan-cancer study confirmed the identification of IGF2BPs as therapeutic targets and highlighted the need to study their association with stemness, and the TME, which contribute to the cancer drug-discovery research. Especially, preliminary studies demonstrate the IGF2BP3 as a potential negative regulator of glioma tumorigenesis by modulating stemness.